2015
DOI: 10.1002/eji.201445057
|View full text |Cite
|
Sign up to set email alerts
|

Recipient expression of ligands for donor inhibitory KIRs enhances NK‐cell function to control leukemic relapse after haploidentical transplantation

Abstract: Keywords: KIR r Haploidentica r HSCT r NK cells r T-cell replete r Leukemia Additional supporting information may be found in the online version of this article at the publisher's web-site

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…Our previous studies demonstrated that NK cell licensing is promoted in unmanipulated haploidentical SCT (haplo-SCT) recipients presenting class I ligands for donor inhibitory KIRs, leading to a decreased relapse rate Zhao et al, 2007Zhao et al, , 2014Zhao et al, , 2015. Further, Sekine et al (2016) demonstrated that cord blood (CB) selection based on the combination of NK cell licensing and activation of KIRs may improve patient outcome after CB transplantation (CBT).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies demonstrated that NK cell licensing is promoted in unmanipulated haploidentical SCT (haplo-SCT) recipients presenting class I ligands for donor inhibitory KIRs, leading to a decreased relapse rate Zhao et al, 2007Zhao et al, , 2014Zhao et al, , 2015. Further, Sekine et al (2016) demonstrated that cord blood (CB) selection based on the combination of NK cell licensing and activation of KIRs may improve patient outcome after CB transplantation (CBT).…”
Section: Discussionmentioning
confidence: 99%
“…Our previously published data have demonstrated that recipient expression of ligands for donor inhibitory KIRs enhances NK cell function to control leukaemic relapse after haploidentical transplantation (Zhao et al, 2014(Zhao et al, , 2015. On this basis, we further demonstrated that CMV reactivation was reduced when donor KIRs were ligated by recipient and donor class I at the same time, when compared with donorhost partnerships in which donor KIRs were ligated by donor but not recipient class I or were ligated by recipient but not donor class I or KIRs that were ligated by neither donor nor recipient class I.…”
Section: Discussionmentioning
confidence: 99%
“…Within the frames of recognition, HLA class I molecules are evolutionally and functionally selected in close correlation with the specificity of the KIR genes (Guinan et al, ; Parham, ; Parham, Norman, Abi‐Rached, & Guethlein, ). In HSC transplant patients, increasing evidence shows that unlike KIR ligand mismatch the cognate HLA:KIR pairings are of primary clinical importance for cancer immunosurveillance, lower relapse incidence and better survival (Gaafar et al, ; Graczyk‐Pol et al, ; Hoseinian et al, ; Nowak et al, , ; Rogatko‐Koroś et al, ; Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to recombination, mutation and adaptive introgression events, numerous HLA molecular polymorphic interfaces are evolutionally selected to encounter specific KIR molecules (Abi‐Rached et al, ; Foley et al, ; Parham & Moffett, ; Pende et al, ; Winter, Gumperz, Parham, Long, & Wagtmann, ). These HLA motifs in malignant patients are crucial for the prediction of HLA:KIR cognate pairs and NK cell function including anti‐leukaemic capacity (Pende et al, ; Rogatko‐Koroś et al, ; Zhao et al, ). Of importance, in HLA molecular interfaces, atypical amino acid combinations and exceptions are possible (De Santis et al, ), leading to cognate HLA:KIR pair misassignments and potential blurry clinical results.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, donor-specific anti-HLA antibodies (DSAs) were indicated to be associated with primary graft failure (GF), transplant-related mortality and inferior overall survival following haplo-HSCT [83]. Donor selection based on other non-HLA systems, such as donor inhibitory killer cell immunoglobulin-like receptors (KIRs), remain to be further elucidated [84].…”
Section: Haploidentical Hematopoietic Stem Cell Transplantation (Haplmentioning
confidence: 99%